Impacts of educational factors on economic growth in regions of China: a spatial econometric approach - Lv, Kangjuan; Yu, Anyu; Gong, Siyi; Wu, Maoguo; Xu, Xiaohong (Technological and Economic Development of Economy, 2017)
This paper investigates the impacts of educational factors on economic growth across 31 provinces during 1996 and 2010 in China. A spatial panel estimation model is applied to study the impacts of education on economic growth taking into account the spatial spillover effects in Feder model and the cumulative effect. The results reveal that (1) educational factors are significantly spatially autocorrelated. Educational factors have spatial spillover effects. Regional differences of education impacts still exist. (2) Average schooling year has a more positive effect on economic output than capital investment and labor force. Basic education might play a more important role in economic growth. (3) Education sector also benefits non-education sectors on economic growth if “spatial effects of economic shocks” are considered. Some policies that may enhance education development and their impacts on economic growth are proposed.First published online: 21 Sep 2015